From “Whipping Boy” to Poster Boy? The Reception of Simmel in Current Critical Theory - Schlitte, Annika (Simmel Studies)

(untitled) (Edizioni ETS, 2025)
This article examines references to Simmel’s thinking in contemporary critical theory. With regard to Axel Honneth’s conception of social philosophy, Rahel Jaeggi’s critique of alienation, and Hartmut Rosa’s resonance theory, it discusses the extent to which the classic reservations against Simmel of earlier critical theory are less relevant in a situation where a broad understanding of capitalism has become established that considers cultural, social, and economic factors in their interaction.